International Continence Society supported pelvic physiotherapy education guideline. Issue 2 (21st February 2018) - Bakker, Els; Shelly, Beth; Esch, Fetske H.; Frawley, Helena; McClurg, Doreen; Meyers, Peter
Abstract : Aim: To provide a guideline of desired knowledge, clinical skills and education levels in Pelvic Physiotherapy (PT). Physiotherapy (PT) involves "using knowledge and skills unique to physiotherapists" and, "is the service only provided by, or under the direction and supervision of a physiotherapist." 1 Methods: The PT Committee, within the body of the International Continence Society (ICS), collected information regarding existing educational levels for pelvic floor PT. Through face to face and on on‐line discussion consensus was reached which was summarized in three progressive educational levels based on knowledge and skills and brought together in a guideline. The guideline was submitted to all physiotherapists and the Educational Committee of the ICS, and after approval, submitted to the Executive Board of the ICS. Result: The guideline lists, in a progressive way, knowledge areas and skills to be achieved by education. It is broad and allows for individual interpretation based on local situations regarding education and healthcare possibilities. It is intended to be dynamic and updated on a regular basis. Conclusion: The proposed Pelvic PT education guideline is a dynamic document that allows course creators to plan topics for continuing course work and to recognize educational level of a therapist in the field of Pelvic PT. This education guideline can be used to set minimum worldwide standards resulting in higher skill levels for local pelvic physiotherapists and thereby better patient care outcome.